Pendidikan Karakter Berbasis Islam sebagai Strategi Preventif Kenakalan Remaja - Feri Rustandi; Asy’ari; Heru Nugraha; Aan Hasanah; Bambang Samsul Arifin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article explores the urgency and strategic role of Islamic-based character education as a preventive approach to juvenile delinquency in the era of globalization. The background of this study is the increasing phenomenon of moral degradation among adolescents, such as bullying, violence, substance abuse, and exposure to negative content in digital media. This qualitative study employs a literature review approach to analyze the concepts, strategies, and implementation of character education rooted in Islamic values. The findings indicate that Islamic character education through integration in the curriculum, teacher role modeling, parental involvement, and the use of Islamic digital media plays a significant role in fostering self-control, responsibility, and moral resilience among youth. Furthermore, practical implementations in Islamic schools and boarding institutions show positive outcomes in reducing deviant behavior and cultivating discipline and ethics. The article concludes that Islamic-based character education is not only an effective moral reinforcement strategy but also a long-term investment for building a virtuous and civilized generation.